PERANAN KEPOLISIAN DALAM PENANGGULANGAN KEJAHATAN YANG DILAKUKAN OLEH ANAK DI WILAYAH KEPOLISIAN SEKTOR BAGAN SINEMBAH ROKAN HILIR - Lantri, Angga Sastiawan; Haryono, Dodi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The increasing levels of crime every year, especially crimes committed by minors, hence the need for legal action, or at least the motivation for them to not be a criminal plaguing the society. Therefore, the role of parents is very important in dealing with child behavior problems. Crime is a term applied to assess the specific actions, as evil deeds. Crime from the perspective of the legal approach is defined as an act that violates the criminal law or the laws in force in the community. Based on the data that the author got from the police sector chart Sinembah districts are 25 (twenty five) cases and 26 (twenty six) children who commit crimes starting from 2012 until 2013 by the of it can be said that the need for the role of police in nenanggulangi problem of crimes committed by children to crimes committed by a child is not growing steadily every year. The purpose of writing the thesis, namely, the First, To Know Factors Affecting Crime ducted by the Son, the Second, To Know The Role of the Police in Crime Prevention ducted by Children in Region Police Sector Chart Sinembah Rokan Hilir, Third, To Know Obstacles in Poverty crime Carried Out By Children in region Police Sector Chart Sinembah Rokan Hilir, and Attempts To Overcome Obstacles in crime Prevention at the Children Who Do By region Police Sector Chart Sinembah Rokan Hilir.